Why the better-than-average effect is a worse-than-average measure of self-enhancement: An investigation of conflicting findings from studies of East Asian self-evaluations - Hamamura, Takeshi; Heine, S.; Takemoto, T. (Springer Netherlands, 2007)
A recent meta-analysis on cross-cultural studies of self-enhancement finds that evidence for East Asian selfenhancement is consistently apparent only in studies where participants compare themselves to the average other, aka the ‘‘Better-than-Average’’ Effect (BAE). However, prior research has suggested that the BAE may conflate motivations to view the self in a positive light with nonmotivational factors, such as a tendency to evaluate ‘‘everyone as better than average’’ [EBTA; Klar Y, Gilladi EE (1997) J Personal Soc Psychol 73:885–901]. In two studies, European-Canadian, Asian-Canadian, and Japanese students were asked to evaluate themselves as well as a fictitious student compared to the average. Replicating prior research, evidence for Japanese self-enhancement was found with the BAE, albeit weaker than Canadians. However, in the measures where the EBTA effect was circumvented, self-enhancement was no longer evident among Japanese. Likewise, within the BAE method, prior research has found that East Asians self-enhance more for important than unimportant traits. When the EBTA effect was circumvented this correlation was also significantly reduced. Findings from this research converge with other sources of evidence that East Asians do not appear to be motivated to self-enhance.